Mapping of optimum operating condition for LiBr-water refrigeration cycles - Mali, Nilesh A.; Bhagwat, Sunil S. (Sadhana: Academy Proceedings in Engineering Sciences, 2017)
In this work, optimum operating condition maps are generated covering wide ranges of refrigeration and sink temperatures for single-and double-effect LiBr-water vapour absorption refrigeration cycle. These optimum condition maps will be useful to choose optimum operating conditions while designing LiBr-water cycle for desired applications. Methodology for generating such maps is discussed in detail, which can also be used for other absorption refrigeration cycles with various working fluids. Three configurations of LiBr-water absorption refrigeration cycles, single effect, double-effect series flow and double-effect parallel flow, are analysed with the most accurate thermodynamic property correlation available in the literature. Sensitivity of cycle performance to various operating variables such as generator, absorber and condenser temperatures is determined. Second law analysis shows that when a higher temperature heat source is available, double-effect cycles are more effective over single effect as they have higher coefficient of performance.